Relationship between exercise self-efficacy, nutritional profile and exercise capacity among postpartum women / Nurul Husna Mohd Nasir - Mohd Nasir, Nurul Husna (2022)
The relationship between exercise self-efficacy and nutritional profile on exercise capacity for the postpartum period has a great impact among postpartum women. Yet, these significant relationships are not well defined or understood, and there is a lack of recent research. The objectives of this study were 1) to determine the socio demographic characteristics, level of exercise self-efficacy, nutritional profile, and exercise capacity among postpartum women, 2) to determine the relationship between socio demographic characteristics, exercise self-efficacy, nutritional profile and exercise capacity among postpartum women 3) to explore the determinants of exercise capacity among postpartum women. A total of 134 postpartum women (mean age = 32 ± 5 years) at Kepala Batas Health Clinic, Penang, were recruited using purposive sampling and performed screening tests before recruitment. Data on socio demographic characteristics, level of exercise self-efficacy (ESE) using Malay translated Self-Efficacy Scale (ESE-M), nutritional profiles and exercise capacity (EC) using the 2-Minutes Step Test (TMST) were been used. The majority of the postpartum women who had a low level of education, low gross monthly income, and living in high-rise residential showed poor ESE level (mean ESE=38.95±22.08, p<.05), (33.2±20.36,p<.001) and (35.71±24.98, p<.05) respectively. Meanwhile, participants with high fat intake, low calcium and fibre intake had low levels of nutritional profile. Participants who recorded poor level of exercise capacity claimed to be have less duration of exercise and barriers to exercise. Analysis of Pearson’s correlation shows that subjects aged 21 to 46 years old, behavior 10 in ESE, overweight and calories intake have a positive relationship with exercise capacity which are the determinants factors in this study. Postpartum women with this factor should receive intervention from a health practitioner especially physiotherapist and dietitian in order to maintain exercise capacity and woman’s fitness.